2009
DOI: 10.7903/cmr.590
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Revenge: Empirical Study of Malaysian Business Employees

Abstract: Building on a previous work by Bradfield and Aquino (1999), this study examines factors influencing forgiveness and revenge cognition and behaviors among Malaysian executives. A questionnaire survey method was undertaken. Respondents were selected by using convenience sampling method from four Malaysian organizations. The findings from this study suggested that 1) that the contemplation of revenge or forgiveness is positively related to their behavioural equivalents: (2) that power asymmetries between the offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(66 reference statements)
0
4
0
1
Order By: Relevance
“…(Bueno Guerra, 2012). According to Ismail, Mohideen, & Togok (2009) revenge is an action in response to some perceived harm or wrongdoing by another party that is intend to inflict damage, injury, discomfort, or punishment on the party judged responsible.…”
Section: Vengeancementioning
confidence: 99%
See 3 more Smart Citations
“…(Bueno Guerra, 2012). According to Ismail, Mohideen, & Togok (2009) revenge is an action in response to some perceived harm or wrongdoing by another party that is intend to inflict damage, injury, discomfort, or punishment on the party judged responsible.…”
Section: Vengeancementioning
confidence: 99%
“…As for the relation between religion and forgiveness, Ismail, et al, (2009) investigated forgiveness cognitions and behaviors in samples of Malaysian Muslim, Christian and Buddhist employees . Results showed that Muslims demonstrated higher correlation between forgiveness cognitions and behaviors followed by Christians.…”
Section: Role Of Age Gender and Culture And Marital Status On Forgiveness And Vengeancementioning
confidence: 99%
See 2 more Smart Citations
“…Quando o poder da pessoa que se percebe objeto de injustiça é menor que o da fonte que ela percebe como geradora da injustiça, a ação de retaliação tende a ser mais indireta, como comportamentos antissociais, de resistência ou de indiferença. (ISMAL;MOHIDEEN;TOGOK, 2009).…”
Section: Retaliaçãounclassified